Unique graphene‐carbon black hybrid nanofiller by a micromechanical cleavage technique as a reinforcing agent in elastomers: Fundamental and experimental studies. Issue 10 (4th January 2023) - Roy, Amrita; Kar, Saptarshi; Ghosal, Ranjan; Mukhopadhyay, Rabindra; Naskar, Kinsuk; Bhowmick, Anil K.
Abstract: In this work, a synthetic technique was developed which effected delamination of graphite into graphene with simultaneous disaggregation of carbon black clusters and formation of secondary attachment between the two. Styrene butadiene rubber nanocomposite with this hybrid filler exhibited substantial reinforcement in the mechanical properties, wear resistance and rubber‐filler interactions. The hybrid nanofiller was superior to conventional carbon black, imparting 57% increase in tensile strength of the nanocomposite. The composite with the hybrid filler also exhibited improved modulus and traction. A detailed analysis of mechanism of reinforcement by the hybrid filler is proposed by the computation of root mean square end‐to‐end network chain distance and the lateral tube dimension employing the entangled‐bound‐rubber‐tube (EBT) model. This neoteric hybrid nanofiller overcame the so‐called dispersibility issues and could be exploited as a part of replacement of carbon black, a synthetic material from fossil fuel by sustainable natural filler. Abstract : Graphene‐carbon black hybrid nanofiller for reinforcement of rubber